Potential of Dianchronous Communication of News Broadcasting on the Example of the TengriTV Online Channel (Herald of Journalism, 2021)
The topic of this study is related to the need to study changes in the usual documentary genres in the context of the new online broadcasting. Today, a chronicle is primarily perceived as a visual document from the past that is used as a quote or illustration in a documentary. However, being a small form of documentary filmmaking, the chronicle became the prototype of the usual news television broadcasting, which today is undergoing changes in online broadcasting, and therefore requires a separate study. The purpose of the study is to discover the possibilities of information broadcasting to continue the traditions of documentary chronicle. The main direction of scientific research was the problem of the identity of the genre of the chronicle in modern conditions. The scientific significance of the study is due to the need to systematize knowledge about the chronicle as a documentary genre in the network broadcast- ing system on the Internet. The practical significance of the work is explained by objective conclusions, which can serve as a basis for the creation of documentaries and information videos, taking into account the need to preserve in them the possibilities for asynchronous communication. The research method- ology is based on a content analysis of informational video materials of the TengtiTV online channel as an example of online broadcasting. The main results of the study show that information videos and recordings of live broadcasts carry the potential of asynchronous communication, and along with this, they have such characteristic features of the chronicle as impersonality and the presence of signs of the time. As a result of the study, it was revealed that online information broadcasting is a «classic» type of chronicle. The important features of the newsreel are such characteristics as impersonality, simple pre- sentation, reflection of the portrait of time, potential for citation.Key words: newsreel, news story, information portal.